HUMOUR IN HRM: A STUDY ON PERCEPTION OF STUDENTS’ ABOUT HUMOROUS TEACHING WITH SPECIAL REFERENCE TO CHENNAI CITY - A. Muqtadirah Begum, Dr. S. Syed Rafiq Ahmed (International Journal of Advanced Science and Technology, 2020)
Humour plays a significant communicative role within organizations. Technology is being progressively integrated into teaching environments in appraisal of enhancing students’ engagement and motivation. In particular, humorous way of teaching systems have been found to foster students’ engagement, enhance classroom dynamics and improve complete students’ learning experience. The purpose of this study was to examine the extent to which students’ perception towards humorous way of teaching. This study carried out quantitative method of 100 respondents of the students in Chennai city. Data collected for the analysis is from both the primary and secondary data. Key findings enriched the quality of student learning in the classroom, with the highest influence on classroom dynamics, engagement, motivation and improved learning experience and also suggest that the use of educational games in the classroom is expected to reduce disruptions, thereby enlightening the quality of teaching and learning away from what is provided in predictable classrooms. Other factors that contributed to students’ higher learning comprised the creation and integration of appropriate content in Chennai, providing students with timely feedback, and game-play (gamification) strategies. Furthermore, teachers should learn to motivate and train humorous activities within their institutions.